(untitled) (Journal of Academic Research, 2026)
This study aimed to identify the indirect relationship between corporate governance principles and improving the quality of financial statements by reducing creative accounting practices in Libyan industrial companies operating in Misrata. To achieve the study’s objectives, a descriptive-analytical approach was employed, using a questionnaire as the data collection tool. The questionnaire was distributed to the study sample, which consisted of all employees working in the financial and administrative departments, as well as internal auditors, within Libyan industrial companies in Misrata. A total of 52 questionnaires were distributed to gather the necessary information. This data was analyzed using the Statistical Package for the Social Sciences (SPSS) and the study’s hypotheses were tested. The study concluded that the principle of "disclosure" was the only principle that fully met the mediating criteria, demonstrating a statistically significant indirect effect of the disclosure variable on the quality of financial statements by reducing creative accounting practices. In contrast, the other principles (the board, the regulatory framework, and shareholders) did not show any statistically significant effect enabling them to achieve this role.